Porphyromonas gingivalis: a potential trigger of neurodegenerative disease - Huang, Ziyan; Hao, Miao; Shi, Naixu; Wang, Xinyu; Yuan, Lin; Yuan, Haotian; Wang, Xiaofeng (Frontiers in Immunology, 2025)
Porphyromonas gingivalis (P. gingivalis) is a gram-negative bacterium and the main causative agent of periodontitis, a disease closely associated with the development of periodontal disease. The progression of periodontitis, a chronic infectious disease, is intricately linked to the inflammatory immune response. Inflammatory cytokines act on periodontal tissues via immunomodulation, resulting in the destruction of the periodontal tissue. Recent studies have established connections between periodontitis and various systemic diseases, including cardiovascular diseases, tumors, and neurodegenerative diseases. Neurodegenerative diseases are neurological disorders caused by immune system dysfunction, including Alzheimer’s and Parkinson’s diseases. One of the main characteristics of neurodegenerative diseases is an impaired inflammatory response, which mediates neuroinflammation through microglial activation. Some studies have shown an association between periodontitis and neurodegenerative diseases, with P. gingivalis as the primary culprit. P. gingivalis can cross the blood-brain barrier (BBB) or mediate neuroinflammation and injury through a variety of pathways, including the gut-brain axis, thereby affecting neuronal growth and survival and participating in the onset and progression of neurodegenerative diseases. However, comprehensive and systematic summaries of studies on the infectious origin of neurodegenerative diseases are lacking. This article reviews and summarizes the relationship between P. gingivalis and neurodegenerative diseases and its possible regulatory mechanisms. This review offers new perspectives into the understanding of neurodegenerative disease development and highlights innovative approaches for investigating and developing tailored medications for treating neurodegenerative conditions, particularly from the viewpoint of their association with P. gingivalis.